Environmental footprints in divergent cuisines: a case study of eight Chinese culinary traditions - Zheng, Jiaqi; Yang, Huijing; Li, Shanghong; Chai, Li (Frontiers in Sustainable Food Systems, 2024)
The sustaiable dietary transitions must account for the varied culinary traditions and regional food cultures to ensure a balanced and culturally sensitive approachThe dietary transition towards environmental sustainability needs to consider the diversity of regional cuisines. This study aims to explore the impact of regional preferences on culinary culture and examine ways to achieve environmentally friendly dietary transitions in China by considering the differences in the environmental burdens of various cuisines. We This study investigates the eight Chinese culinary traditions and depicts their respective popularity in China at the city level via POI characterization based on ArcGIS. Water, carbon, and ecological footprints are selected to investigate the environmental performance of each type of cuisine. Results show that the eight cuisines vary significantly in spreads of influence and environmental performances. Chuan Cuisine, the nationally distributed cuisine in China, brings the least environmental burden. Chuan cuisine is the most widely disseminated cuisine with a relatively low environmental burden. The remaining seven cuisines have limited spreads of influence and are mainly distributed in small cultural regions and the surrounding areas. Hui Cuisine, Zhe Cuisine, and Min Cuisine have the worst environmental performances. This study reveals the significant impact of regional cuisines on the environmental footprint of diets and highlights the necessity of considering this impact when promoting dietary transition, especially in those culturally diverse countries.